Live-cell imaging of G-actin dynamics using sequential FDAP - Kiuchi, Tai (Landes Bioscience, 2011)
Various microscopic techniques have been developed to understand the mechanisms that spatiotemporally control actin filament dynamics in live cells. Kinetic data on the processes of actin assembly and disassembly on F-actin have been accumulated. However, the kinetics of cytoplasmic G-actin, a key determinant for actin polymerization, has remained unclear because of a lack of appropriate methods to measure the G-actin concentration quantitatively. We have developed two new microscopic techniques based on the fluorescence decay after photoactivation (FDAP) time-lapse imaging of photoswitchable Dronpa-labeled actin. These techniques, sequential FDAP (s-FDAP) and multipoint FDAP, were used to measure the time-dependent changes in and spatial distribution of the G-actin concentration in live cells. Use of s-FDAP provided data on changes in the G-actin concentration with high temporal resolution; these data were useful for the model analysis of actin assembly processes in live cells. The s-FDAP analysis also provided evidence that the cytoplasmic G-actin concentration substantially decreases after cell stimulation and that the extent of stimulus-induced actin assembly and cell size extension are linearly correlated with the G-actin concentration before cell stimulation. The advantages of using s-FDAP and multipoint FDAP to measure spatiotemporal G-actin dynamics and the roles of G-actin concentration and ADF/cofilin in stimulus-induced actin assembly and lamellipodium extension in live cells are discussed.